News frames and national security : covering big brother - McLeod, Douglas Malcolm; Shah, Dhavan V.; Cambridge eBooks (Cambridge : Cambridge University Press, 2015)
Did media coverage contribute to Americans' tendency to favor national security over civil liberties following the 9/11 attacks? How did news framing of terrorist threats support the expanding surveillance state revealed by Edward Snowden? Douglas M. McLeod and Dhavan V. Shah explore the power of news coverage to render targeted groups suspicious and to spur support for government surveillance. They argue that the tendency of journalists to frame stories around individual targets of surveillance - personifying the domestic threat - shapes citizens' judgments about tolerance and participation, leading them to limit the civil liberties of a range of groups under scrutiny and to support 'Big Brother'.
Preface : The Story of this Book -- Understanding Message Framing and Effects -- Framing Surveillance and the War on Terror -- Designing the Studies (with Lucy Atkinson, Seungahn Nah, and Hyunseo Hwang) -- Converging Cues and the Spread of Activation (with Jaeho Cho and Homero Gil de Zuniga) -- Cognitive Complexity and Attitude Structure (with Hyunseo Hwang, Jaeho Cho, Seungahn Nah, and Nam-Jin Lee) -- Security Concerns and Tolerance Judgments (with Heejo Keum and Hernando Rojas) -- Group Perceptions and Expressive Action (with Michael G. Schmierbach, Michael P. Boyle, and Cory L. Armstrong) -- Covering "Big Brother" -- Appendix A: Measurement Details for Arab Study -- Appendix B: Measurement Details for Response Latency -- Appendix C: Measurement Details for Activist Study: Closed-ended Responses -- Appendix D: Measurement Details for Activist Study: Open-ended Responses.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Mass media -- Political aspects -- United States; Mass media -- Influence -- Case studies; Mass media policy -- United States; Communication in politics -- United States; National security -- United States; Terrorism -- United States -- Prevention; Electronic surveillance -- United States -- Public opinion; Privacy, Right of -- Public opinion; Civil rights -- United States; Electronic books